2016
DOI: 10.3314/mmj.16-00019
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Diagnosis of <I>Pneumocystis</I> Pneumonia

Abstract: Pneumocystis jirovecii is a prototypical opportunistic pathogen, causing an asymptomatic or mild infection in normal hosts and fulminating pneumonia(Pneumocystis pneumonia, PCP)in immunocompromised hosts. PCP is a leading cause of morbidity and mortality in immunocompromised patients such as AIDS patients. Microscopic detection of cysts and trophic forms of P. jirovecii in respiratory secretions is simple and useful but may underestimate the P. jirovecii infection. Conventional polymerase chain reaction(PCR)an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 46 publications
0
15
0
3
Order By: Relevance
“…Second, the diagnosis of PCP was mainly based on elevated levels of β-D-glucan and the detection of P. jirovecii by PCR. Although β-D-glucan is a useful serological marker for PCP diagnosis (Li et al 2015;Song et al 2016), colonization by P. jirovecii, as detected by a PCR method, has also been reported (Alanio and Bretagne 2017). Mori et al (2009) reported that 10.9% of asymptomatic carriers of P. jirovecii could be identified by PCR using the sputum or BALF of patients with RA, all of whom had received MTX.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the diagnosis of PCP was mainly based on elevated levels of β-D-glucan and the detection of P. jirovecii by PCR. Although β-D-glucan is a useful serological marker for PCP diagnosis (Li et al 2015;Song et al 2016), colonization by P. jirovecii, as detected by a PCR method, has also been reported (Alanio and Bretagne 2017). Mori et al (2009) reported that 10.9% of asymptomatic carriers of P. jirovecii could be identified by PCR using the sputum or BALF of patients with RA, all of whom had received MTX.…”
Section: Discussionmentioning
confidence: 99%
“…je osjetljivost veća od 85 % i specifičnost veća od 90 % 3 . Za razlikovanje kolonizacije od infekcije od koristi je PCR u realnom vremenu, iako ciljani geni i referentne vrijednosti još uvijek nisu u potpunosti utvrđeni 8 . Inducirani iskašljaj je najprikladniji uzorak za analizu, s obzirom na to da se dobiva najmanje invazivnim putem, a osjetljivost mu se kreće između 50 -90 %.…”
Section: Prikaz Slučajaunclassified
“…Također, prisutnost ground glass areala na HRCT-u nije specifična za PJP, međutim, njihova odsutnost snažno sugerira da nije riječ o PJP-u 5 . Osim opisanih, kao pomoćna metoda u detektiranju PJP-a može poslužiti i određivanje beta-D-glukana u serumu, s obzirom na to da je to sastojak gljivične stijenke 8 . Budući da je bolest brzo dijagnosticirana zahvaljujući molekularnoj dijagnostici (PCR) te je i odgovarajuće liječenje na vrijeme započeto, pacijentica je ozdravila od PJP-a.…”
Section: Prikaz Slučajaunclassified
“…Until recently, the definitive diagnosis of PCP required the microcscopic examination of bronchial lavage or induced sputum specimens for the direct visualization of Pneumocystis organisms . The need for both bronchoscopy and an experienced microscopist precluded its use in many low‐resource settings, hence the historically low‐rate of reported PCP in low‐income settings .…”
Section: Diagnosis and Assessmentmentioning
confidence: 99%